Addressing HIV-Related Intersectional Stigma and Discrimination to Improve Public Health Outcomes: An AJPH Supplement - Dale, Sannisha K.; Ayala, George; Logie, Carmen H.; Bowleg, Lisa (American Journal of Public Health, 2022)
Intersectional stigma and discrimination (ISD) pose critical barriers to HIV services and drive HIV inequities. This AJPH supplement represents a combination of research, theoretical articles, and community insights to move the field toward actions to reduce ISD. This focus builds on scholarship on stigma and HIV published in AJPH. In 1987, six years afterthe start of the US HIV epidemic, Kelly et al.1 used case vignettes in which patients were described as having either AIDS or leukemia and being either heterosexual or gay to measure physicians' stigma. They concluded, "While some attitude negativity was anticipated, the strength and consistency of the stigmatization was disquieting."1(p790) Also, before intersectionality was explicitly discussed in the HIV field, researchers were documenting the impact of multiple forms of stigma among sexual minority men.2,3 AJPH has since published more than 800 articles addressing HIV and stigma,4 illustrating that HIV-related stigma remains a persistent challenge to ending the HIV epidemic.